Association between fulfilling the recommendations for health-enhancing physical activity with (instrumental) activities of daily living in older Austrians - Crevenna, Richard (Wien Klin Wochenschr, 2019)
AIM: The aim of the study was to describe the association between fulfilling the recommendation for health-enhancing physical activity (PA), and deficits in activities of daily living (ADL) and instrumental activities of daily living (IADL) in 3308 subjects aged 65+ years from the Austrian Health Interview Survey 2014. METHODS: The proportion of subjects who fulfilled the minimal recommendations for health-enhancing PA was assessed with the Physical Activity Questionnaire of the European Health Interview Survey (EHIS-PAQ). The ADLs were assessed based on the Barthel index, and IADLs by the IADL scale of Lawton and Brody. Additionally, various sociodemographic and health-related factors were assessed. RESULTS: Of the participants 54.7% did not fulfil the minimal requirements for aerobic PA, and 67.1% not for muscle strengthening PA, 16.4% reported ADL deficits, and 47.1% IADL deficits. Adjusted for sociodemographic and health-related parameters, not fulfilling the recommendations for aerobe PA was associated with a higher chance for ADL deficits (odds ratio, OR 1.73, 95%-confidence interval 1.36–2.21), and IADL deficits (1.57; 1.34–1.84). Not fulfilling the recommendations for muscle strengthening PA also increased the chance for ADL and IADLs deficits (1.34; 1.04–1.72, and 1.29; 1.09–1.53, respectively). CONCLUSION: The number of participants who did not fulfil the minimal requirements for aerobic or strengthening PA was very high, and these participants showed significantly more problems in ADLs and IADLs. Therefore, all future efforts should focus on increasing participation and adherence in exercise programs for older people with the intention to improve their performance status and functions in daily life.